Prediction of osteoporosis from proximal femoral cortical bone thickness and Hounsfield unit value with clinical significance - Xu, Gaoxiang; Wang, Daofeng; Zhang, Hao; Xu, Cheng; Li, Hua; Zhang, Wupeng; Li, Jiantao; Zhang, Licheng; Tang, Peifu (Frontiers in Surgery, 2023)
Background Utilizing dual-energy x-ray absorptiometry (DXA) to assess bone mineral density (BMD) was not routine in many clinical scenarios, leading to missed diagnoses of osteoporosis. The objective of this study is to obtain effective parameters from hip computer tomography (CT) to screen patients with osteoporosis and predict their clinical outcomes. Methods A total of 375 patients with hip CT scans for intertrochanteric fracture were included. Among them, 56 patients possessed the data of both hip CT scans and DXA and were settled as a training group. The cortical bone thickness (CTh) and Hounsfield unit (HU) values were abstracted from 31 regions of interest (ROIs) of the proximal femur. In the training group, the correlations between these parameters and BMD were investigated, and their diagnostic efficiency of osteoporosis was assessed. Finally, 375 patients were divided into osteoporotic and nonosteoporotic groups based on the optimal cut-off values, and the clinical difference between subgroups was evaluated. Results The CTh value of ROI 21 and the HU value of ROI 14 were moderately correlated with the hip BMD [r = 0.475 and 0.445 (p < 0.001), respectively]. The best diagnostic effect could be obtained by defining osteoporosis as CTh value < 3.19 mm in ROI 21 or HU value < 424.97 HU in ROI 14, with accuracies of 0.821 and 0.883, sensitivities of 84% and 76%, and specificities of 71% and 87%, respectively. The clinical outcome of the nonosteoporotic group was better than that of the osteoporotic group regardless of the division criteria. Conclusion The CTh and HU values of specific cortex sites in the proximal femur were positively correlated with BMD of DXA at the hip. Thresholds for osteoporosis based on CTh and HU values could be utilized to screen osteoporosis and predict clinical outcomes.